Can symbiotic fungi protect plants from insect pests? A simple mathematical model. Issue 6 (16th September 2020) - Atlihan, Remzi; Britton, Nicholas F.; Demir, Semra; Papasidero, Annalisa; Risvanli, Mehmet Ramazan; Seminara, Manuela; Venturino, Ezio
Abstract : A mathematical model is proposed for simulating and understanding the relationship between the potato plant and its most significant pest, the Colorado potato beetle, when mediated by mycorrhiza, a symbiotic plant‐fungus association. From its analysis it is seen that, quite counterintuitively, an overabundant use of mycorrhiza for enhancing productivity is rather detrimental, in that it triggers persistent oscillations in the foliage and the population of the beetle, giving an instance of the paradox of enrichment. Some indications for biological pest control arise from the investigation of the bifurcations that occur in the model ecosystem.